2009
DOI: 10.3855/jidc.549
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and demographic characterization of invasive isolates of Salmonella Typhimurium in HIV co-infected patients in South Africa

Abstract: Background: Non-typhoidal Salmonella are frequently food-borne zoonotic pathogens that may cause invasive disease in HIV-positive individuals. Methodology: Invasive isolates (n = 652) of Salmonella Typhimurium from human patients in Gauteng Province of South Africa were investigated for the years 2006 and 2007. Bacteria were identified using standard microbiological techniques and serotyping was performed using commercially available antisera. Susceptibility testing to antimicrobial agents was determined by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…In South Africa, the major contributing factor to invasive salmonellosis is HIV infection [20]: the introduction of ART is thus critical to preventing iNTS infections. We examined the incidence of iNTS in Gauteng Province, which has a predominantly urbanised population, and documented a significant decrease in the incidence of iNTS cases in a period of increased ART utilization which followed the introduction of ART in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, the major contributing factor to invasive salmonellosis is HIV infection [20]: the introduction of ART is thus critical to preventing iNTS infections. We examined the incidence of iNTS in Gauteng Province, which has a predominantly urbanised population, and documented a significant decrease in the incidence of iNTS cases in a period of increased ART utilization which followed the introduction of ART in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…primarily occurs via consumption of food and water that is contaminated with fecal pollution (animal and human) (Keddy et al, 2009). Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, non-typhoidal Salmonella was isolated from up to 35% of HIV-infected African adults with documented bloodstream infections and mortality rate of 35 -60% (Hohmann, 2001;Kankwatira et al, 2004). Keddy et al (2009) reported S. typhimurium as a major opportunistic pathogen particularly in HIV-positive individuals.…”
Section: Epidemiology Of Human Non-typhoidal Salmonellosismentioning
confidence: 99%